One Health Advances - Shen, Jianzhong; Schwarz, Stefan; Wang, Yang.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
One Health Advances focuses on the intersection of animal, human, and environmental health. The journal aims to bring together researchers, practitioners and policy-makers from the fields of veterinary and human medicine & health, the food sector and the environment by providing a platform to advance knowledge, techniques and strategies in the global public health. The journal is committed to publish original research articles, reviews, editorials, comments, and correspondences, preferably in a collaborative and multi-disciplinary manner. All articles are rigorously peer-reviewed based on relevance and quality. Topics of interest include but are not limited to: (1) Antimicrobial resistance (AMR): Topics related to antibacterial, antiviral, antifungal, and antiparasitic resistance. (2) Animal-derived food safety: The risks of hazardous chemicals and microorganisms in animal-derived food pose serious risks to public health and the environment. (3) Zoonoses: Topics related to epidemiology, etiology, biology, diagnostics, prevention, treatment, and management of zoonotic diseases. (4) Animal diseases: Researches related to veterinary medical knowledge and clinical practices of companion animal and food animal, preferably topics explore challenges and guarantee of animal health and that of humans in contact with them.
Keywords: Veterinary medicine; Medicine, Preventive; Health promotion; Veterinary microbiology; Food$1 (BSafety measures.s; Animal culture; Veterinary Science; Health Promotion and Disease Prevention; Veterinary Microbiology; Food Safety; Animal Science